Pharmacological Management of Pediatric Kerion Celsi. (October 2013) - Pranteda, G.; Muscianese, M.; Grimaldi, M.; Tuzi, M.; Pranteda, G.; Fidanza, L.; Tamburi, F.; Bottoni, U.; Nisticò, S.
We report a case of severe tinea capitis, treated successfully with griseofulvin. In our opinion, the treatment of this severe dermatophytosis with griseofulvin is safe and effective. Other treatments, such as itraconazole pulsed therapy, failed, despite an initial improvement, leading to an aggressive recurrence of the lesion. We chose griseofulvin for its well-known large spectrum activity, also against uncommon species, like Microsporum Gypseum, which are responsible for the most severe cases.